The molecular systematics of Southern African Testudinidae - Varhol, Richard Joseph (Division of Chemical Pathology, 2018)
Sixteen of the world's 42 species of land tortoises occur in Africa, 10 of which are endemic to southern Africa. South Africa itself, which occupies 0.8% of the earth's total land mass, has the highest tortoise biodiversity in the world, with 13 species. This is the first study to use molecular techniques to investigate the evolutionary history of this group, which displays an unusually high level of speciation on the continent. Four hundred and fifty base pairs of mtDNA cytochrome b sequence were obtained, using direct PCR-based sequencing, from 32 individual tortoise blood samples, comprising 13 different species from 6 genera. PAUP 3. 1.1, and MEGA were used to infer a phylogeny using Chrysemys scripta elegans (an Emydid) an outgroup. Both phenetic and cladistic methods generated similar results. With the exception of Malacochersus, both morphological and molecular work show largely congruent results. When intra-specific relationships, using the molecular results, were compared to the existing morphological data, Psammobates was the only genus with a consistent topology. Proposals for the re-evaluation of Homopus, Kinixys and Geochelone have been made. Suggestions, based on molecular results, include the distinction between Chersobius and Homopus (Hewitt 1937), incorporating Malacochersus tornieri into Kinixys, and the elevation of Geochelone pardalis pardalis and G.p. babcocki to species level. Sequencing a further nine individuals within Homopus areolatus showed a higher than expected sequence variation, suggesting a distinct population structure and possibly cryptic species.